2011
DOI: 10.1080/09603123.2010.544033
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of particulate matter (PM2.5) on respiratory mortality in Madrid

Abstract: Our results reflect the association that exists between PM(2.5) concentrations and daily respiratory-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 35 publications
3
67
1
5
Order By: Relevance
“…Compared with short-term associations between fine particles and mortality reported for individual European cities, our pooled estimates of associations with a 10-μg/m 3 increase in PM 2.5 were weaker than those reported for Barcelona [for all-cause mortality, Perez et al (2008) reported a 3.20% increase, whereas Ostro et al (2011) reported a 1.40% increase] and Madrid [2.80% increase in respiratory mortality for a single-day exposure (Guaita et al 2011) and a similar increase in deaths from circulatory causes (Maté et al 2010)]. However, Atkinson et al (2010) reported no evidence of associations between PM 2.5 and all-cause or cardiovascular mortality in London.…”
Section: Discussioncontrasting
confidence: 87%
“…Compared with short-term associations between fine particles and mortality reported for individual European cities, our pooled estimates of associations with a 10-μg/m 3 increase in PM 2.5 were weaker than those reported for Barcelona [for all-cause mortality, Perez et al (2008) reported a 3.20% increase, whereas Ostro et al (2011) reported a 1.40% increase] and Madrid [2.80% increase in respiratory mortality for a single-day exposure (Guaita et al 2011) and a similar increase in deaths from circulatory causes (Maté et al 2010)]. However, Atkinson et al (2010) reported no evidence of associations between PM 2.5 and all-cause or cardiovascular mortality in London.…”
Section: Discussioncontrasting
confidence: 87%
“…Nevertheless, previous studies have found short-term exposure to ambient pollutants can also lead to respiratory-associated mortality (Garrett and Casimiro, 2011;Guaita et al, 2011). Future work should consider the effect of the short-term exposure, perhaps by using the explicit approach to characterize short-term peak of the pollutants.…”
Section: Limitations and Future Workmentioning
confidence: 93%
“…Wiele prac prowadzonych w ostatnich latach pokazuje, że drobne cząstki emitowane do środowiska rów-nież mogą przyczynić się do powstawania niekorzystnych skutków zdrowotnych w układzie oddechowym i sercowo-naczyniowym człowieka (17)(18)(19)(20)(21). W pracy przeglądowej Kim i wsp.…”
Section: Omówienieunclassified